Pemberian Sanksi Pidana Terhadap Pelaku Tindak Pidana Pedofilia Dalam Sistem Hukum Di Indonesia - TP Siregar, Gomgom (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2023)
Crimes against children continue to be rampant in Indonesia, the government also does not remain silent in prevention efforts, the community also participates in showing its concern for victims who afflict children. Many experts propose that perpetrators of crimes against children, especially pedophilia, be sentenced to death, castration or at least life in prison. Child sexual abuse can include contact or interaction between a child and an adult, where the child is used for sexual stimulation by the perpetrator or another person in a position of power or control over the victim, including inappropriate physical contact, making pornography or exposing the vital/genital organs of an adult to a child. Pedophilia as a disorder or mental disorder in a person to act by making children the instrument or target of that action. Generally, the form of action is in the form of sexual lust. This act of sexual abuse is very troubling because the victims are children. This sexual abuse causes psychological trauma that cannot be healed in a short time. The results of the study, namely the regulation of criminal acts of pedophilia on children used in imposing sanctions on pedophile offenders in Indonesia in accordance with Indonesian Criminal Law, namely the Criminal Code and Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Protection of Children. Keywords: Criminal Sanctions, Crime, Pedophilia